Evaluation of Physical Expansion of Built Environment in District Sargodha (Pakistan) (Journal of Asian Development Studies, 2023)
The current research delves into a comprehensive evaluation of the built-up area change within District Sargodha, Pakistan. This research evaluated the expansion of built-up area infrastructure in the study area and the contributing physical features. The expansion is evaluated through satellite imageries of the last three decades, focusing on 1993, 2003, 2013, and 2023 as study years. To avoid irregular and uneven expansion of built-up areas, monitoring of such growth is inevitable. The physical growth of the built environment in Sargodha district has exhibited remarkable trends from 1993 to 2023. Various factors contributing to urbanization, including industrial units, commercial zones, transportation networks, and health and educational institutions, have witnessed significant expansion during the study period in the study area. In 1993, the built-up area comprised 308.2 km2 , representing 5% of the district's total area. Subsequent years saw substantial growth as by 2003, the built-up area reached 453.6 km2 (8% of the total area). By 2013, it expanded to 541.3 km2 (9%) and by 2023, the built-up area also accelerated to 765 km2 (13%). This growth was accompanied by a noticeable shift in population dynamics, signifying a noteworthy trend of urbanization. Conversely, the rural population decreased, likely driven by enhanced economic prospects and improved urban living conditions.